Google adwords for dummies ebook - Jacobson, Howie (Dummies., 2011)
The fun and friendly guide on getting the most value out of your AdWords campaigns, now updated! Google AdWords is a unique tool that allows you to set your own budget and create ads and choose keywords that are specifically related to your business. This handy guide walks you through the newest tips, tricks, and techniques for maximizing your AdWords campaign. Presenting coverage that is nearly entirely rewritten or revised, this practical guide adds chapters on topics such as ad extensions, feeds for e-commerce, mobile advertising, advanced ad writing, and the new Google display network. In addition, the author provides updates that reflect helpful new best practices. Boasts approximately 85 percent updated or new content Updates popular topics such as experiments, ad extensions, feeds for e-commerce, mobile advertising, advanced ad writing, and more Incorporates changes to the AdWords interfaces Shares best practices in split testing, opt-in landing page structure, and ad group structure Reviews new, free tools included in AdWords as well as new and improved third-party tools With this handy reference by your side, you'll discover the best way to make a Google AdWords campaign to work for you !